Analysis method of important structural parameters of four-point contact ball bearing - WANG Yanshuang; ZHANG Chenxu; WANG Mingwei; WANG Zijun; WANG Gaofeng; LI Wenbin; ZHANG Shuyu (Jixie chuandong)
ObjectiveBased on the analysis of the contact mechanics characteristics of four-point contact ball bearings, the important structural parameters of the bearings, including the contact angle, groove curvature radius coefficient, and radial clearance, were designed，and the influence of the bearing structural parameters on the sub-surface stress of the bearing raceway was comprehensively considered to provide new reference for the design of four-point contact ball bearings.MethodsBy establishing a high-precision multi-body contact dynamics model of four-point contact ball bearings and using the finite element analysis method to analyze the subsurface stress and hardened layer depth of the bearing raceway, the rationality of the design was further verified.ResultsThe results show that the larger the initial contact angle is, the larger the bearing capacity will be, the smaller the sub-surface stress peak and the required minimum hardened layer depth will be, but the ellipse truncation will be easier to occur. It is recommended to select the smaller value of 45°-50° as the initial contact angle. The smaller the coefficient of groove curvature radius is, the larger the bearing capacity will be, the smaller the sub-surface stress and the minimum hardened layer depth will be, and the recommended value of groove curvature radius coefficient shall be in the range of 0.52-0.53. As the clearance decreases, the stress on the left side of the inner ring increases slightly, while the stress on the right side decreases. The optimal clearance is -0.03 mm.